TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

The British Columbia Farmers’ Market Nutrition Coupon Program Reduces Short-Term Household Food Insecurity Among Adults With Low Incomes: A Pragmatic Randomized Controlled Trial - Michelle L. Aktary; Sharlette Dunn; Tolulope Sajobi; Heather O’Hara; Peter Leblanc; Gavin R. McCormack; Stephanie Caron-Roy; Yun Yun Lee; Raylene A. Reimer; Leia M. Minaker; Kim D. Raine; Jenny Godley; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Age distribution of groundwater in fractured aquifers of the St. Lawrence Lowlands (Canada) determined by environmental tracers (3H/3He, 85Kr, SF6, CFC-12, 14C) - G. Meyzonnat; S. Musy; J. A. Corcho-Alvarado; F. Barbecot; D. L. Pinti; R. Purtschert; J.-M. Lauzon; R. McCormack (Hydrogeology Journal, 2023)

Evaluation of calibration approaches for indoor deployments of PurpleAir monitors - Kirsten Koehler; Megan Wilks; Timothy Green; Ana M. Rule; Misti L. Zamora; Colby Buehler; Abhirup Datta; Drew R. Gentner; Nirupama Putcha; Nadia N. Hansel; Gregory D. Kirk; Sarath Raju; et al. (Atmospheric Environment, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Safeguarding marine life: conservation of biodiversity and ecosystems - Delphi Ward; Jessica Melbourne-Thomas; Gretta T. Pecl; Karen Evans; Madeline Green; Phillipa C. McCormack; Camilla Novaglio; Rowan Trebilco; Narissa Bax; Madeleine J. Brasier; Emma L. Cavan; Graham Edgar; et al. (Reviews in Fish Biology and Fisheries, 2022)
Marine ecosystems and their associated biodiversity sustain life on Earth and hold intrinsic value. Critical marine ecosystem services include maintenance of global oxygen and carbon cycles, production of food and energy, and sustenance of human wellbeing. However marine ecosystems are swiftly being degraded due to the unsustainable use of marine environments and a rapidly changing climate. The fundamental challenge for the future is therefore to safeguard marine ecosystem biodiversity, function, and adaptive capacity whilst continuing to provide vital resources for the global population. Here, we use foresighting/hindcasting to consider two plausible futures towards 2030: a business-as-usual trajectory (i.e. continuation of current trends), and a more sustainable but technically achievable future in line with the UN Sustainable Development Goals. We identify key drivers that differentiate these alternative futures and use these to develop an action pathway towards the desirable, more sustainable future. Key to achieving the more sustainable future will be establishing integrative (i.e. across jurisdictions and sectors), adaptive management that supports equitable and sustainable stewardship of marine environments. Conserving marine ecosystems will require recalibrating our social, financial, and industrial relationships with the marine environment. While a sustainable future requires long-term planning and commitment beyond 2030, immediate action is needed to avoid tipping points and avert trajectories of ecosystem decline. By acting now to optimise management and protection of marine ecosystems, building upon existing technologies, and conserving the remaining biodiversity, we can create the best opportunity for a sustainable future in 2030 and beyond.

Effects of early life stress on cocaine intake in male and female rhesus macaques - Alison G. P. Wakeford; Brik Kochoian; Erin R. Siebert; Sarah Katznelson; Elyse L. Morin; Brittany R. Howell; Kai M. McCormack; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of early life stress on cocaine self-administration in post-pubertal male and female rhesus macaques - Alison G. P. Wakeford; Elyse L. Morin; Sara N. Bramlett; Brittany R. Howell; Kai M. McCormack; Jerrold S. Meyer; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2019)

The mitochondrial genome of Octostruma stenognatha and its phylogenetic implications - P. R. Ströher; E. Zarza; W. L. E. Tsai; J. E. McCormack; R. M. Feitosa; M. R. Pie (Insectes Sociaux, 2017)

Mycorrhizal fungi and roots are complementary in foraging within nutrient patches - Lei Cheng; Weile Chen; Thomas S. Adams; Xing Wei; Le Li; Michael Luke McCormack; Jared L. DeForest; Roger T. Koide; David M. Eissenstat (Ecology, 2016)
The roots of the majority of tree species are associated with either arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi. The absorptive roots of tree species also vary widely in their diameter. The linkages between root thickness, mycorrhiza type and nutrient foraging are poorly understood. We conducted a large root ingrowth experiment in the field to investigate how absorptive roots of varying thickness and their associated fungi (AM vs. EM) exploit different nutrient patches (inorganic and organic) in a common garden. In nutrient‐rich patches, thin‐root tree species more effectively proliferated absorptive roots than thick‐root tree species, whereas thick‐root tree species proliferated more mycorrhizal fungal biomass than thin‐root tree species. Moreover, nutrient patches enriched with organic materials resulted in greater root and mycorrhizal fungal proliferation compared to those enriched with inorganic nutrients. Irrespective of root morphology, AM tree species had higher root foraging precision than mycorrhizal hyphae foraging precision within organic patches, whereas EM tree species exhibited the opposite. Our findings that roots and mycorrhizal fungi are complementary in foraging within nutrient patches provide new insights into species coexistence and element cycling in terrestrial ecosystems.

Mycorrhizal and rhizomorph dynamics in a loblolly pine forest during 5 years of free‐air‐CO 2 ‐enrichment - S. G. PRITCHARD; A. E. STRAND; M. L. McCORMACK; M. A. DAVIS; R. OREN (Global Change Biology, 2008)
Soil fungi couple plant and ecosystem resource demands to pools of soil resources. Research on these organisms is needed to predict how rising atmospheric CO 2 will influence forest ecosystem processes and soil carbon (C) sequestration potential. We examined the influence of free‐air‐CO 2 ‐enrichment (FACE) on mycorrhizal and extraradical rhizomorph dynamics over a 5‐year period in a loblolly pine forest using minirhizotrons. Standing crop of mycorrhizal root tips varied greatly spatially and through time. Summed across all years, CO 2 enrichment increased mycorrhizal root tip production by 194% in deep soil (15–30 cm) but did not influence mycorrhizal production in shallow soil (0–15 cm). Production and mortality of soil rhizomorph length was 27% and 25% greater in CO 2 ‐enriched plots compared with controls over a 5‐year period beginning in January of 2000 and running through autumn 2004. Effects of atmospheric CO 2 enrichment on longevity of mycorrhizal root tips and rhizomorphs varied with soil depth (mycorrhizae and rhizomorphs) and with diameter (rhizomorphs). For instance, survival of mycorrhizal tips was reduced in CO 2 ‐enriched plots in deep soil (15–30 cm depth) but was increased in shallower soil (0–15 cm). Rhizomorph turnover was accelerated in shallow soil but effects on survivorship in deep soil varied according to diameter. A drought in 2002 coupled with loss of leaf area to an ice storm late in 2002 were followed by reductions in rhizomorph and mycorrhizal production, increases in mortality, and decreases in standing crop during 2003 and 2004. These effects tended to be more severe in CO 2 ‐enriched plots. Positive effects of atmospheric CO 2 enrichment on mycorrhizal fungi, primarily observed in deeper soil, are probably contributing to the prolonged stimulation of NPP by CO 2 enrichment at the Duke FACE study site.

Novel phenotypes identified by plasma biochemical screening in the mouse - Tertius A. Hough; Patrick M. Nolan; Vicky Tsipouri; Ayo A. Toye; Ian C. Gray; Michelle Goldsworthy; Lee Moir; Roger D. Cox; Sian Clements; Peter H. Glenister; John Wood; Rachael L. Selley; et al. (Mammalian Genome, 2002)

Informatics for mutagenesis: the design of Mutabase—a distributed data recording system for animal husbandry, mutagenesis, and phenotypic analysis - Mark A. Strivens; Rachel L. Selley; Simon J. Greenaway; Mazda Hewitt; Xinhong Liu; Kirstin Battershill; Stefan L. McCormack; Karen A. Pickford; Lucie Vizor; Patrick M. Nolan; A. Jacqueline Hunter; Josephine Peters; et al. (Mammalian Genome, 2000)